(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
شَهِد الاقتصاد السوري في السنوات الأربع الماضية معدل نمو مقبولاً، وصل بالمتوسط إلى 5% رغم الأزمة المالية العالمية، وعدوان إسرائيل على المنطقة، وهذا النمو لم يكن بسبب المساعدات العربية أو الدولية، بل كان بسبب رفع نسبة الاستثمار من 18% إلي 25% من الناتج المحلي، ولكن هذه الزيادة في النمو لم تكن كافية لمعالجة مشكلات الجانب الاجتماعي لاقتصاد السوق، الذي تبنته الحكومة السورية بعد المؤتمر العاشر للحزب، إذ لم يعالج هذا النمو- والذي كان لبعض القطاعات الخدمية، على حساب قطاعات إنتاجية مثل الزراعة والصناعة- مشكلات البطالة المرتفعة، وسوء توزيع الدخل رغم الزيادات التي أصابت الرواتب والأجور، وانتشار الفقر، وانخفاض إنتاجية العامل نتيجة ضعف التأهيل والتدريب، ويتم اليوم طرح فكرة التشاركية بين القطاعين العام والخاص في جميع المستويات للاستفادة من خبرات القطاع الخاص في خلق فرص عمل ورفع الإنتاجية القومية للوصول إلى تنمية شاملة لجميع القطاعات. The Syrian economy has witnessed a growth rate acceptable in the past four years; it reached an average of 5% despite global financial crisis and Israel’s aggression on the region, and this growth was not because of Arab or international aid, but was due to the raise of the investment ratio from 18% to 25% of the GDP, but this increase in growth were not sufficient to address the problems of the social aspect of the market economy adopted by the Syrian government after the Tenth Congress of Al-Baa’th Party, so that this growth - which was of some service sectors at the expense of productive sectors such as agriculture and industry - did not address the problems of high unemployment and poor income distribution, despite the increases of the salaries and wages, and this growth did not address the widespread poverty, low worker productivity as a result of lack of skills and training, the partnerships between public and private sectors to be put at all levels, to benefit from the experiences of the private sector in creating job opportunities and raise national productivity for comprehensive development access of all sectors.